Life in the Iron Mills - Davis, Rebecca Harding, 1831-1910 (Book collections on Project MUSE., 2020)
"Edited and with a biographical interpretation by Tillie Olsen, Rebecca Harding Davis's Life in the Iron Mills is a Feminist Press classic, and a look at working-class lives and factory conditions during the American Industrial Revolution in the nineteenth century. This reissue includes a new foreword written by labor journalist Kim Kelly"--